Ten Emerging Trends in the Epidemiology of Diabetic Retinopathy. (3rd July 2016) - Sabanayagam, Charumathi; Yip, WanFen; Ting, Daniel S. W.; Tan, Gavin; Wong, Tien Y.
ABSTRACT: Purpose : Diabetes is a major public health problem affecting 415 million people worldwide. With the increasing prevalence of diabetes, diabetic retinopathy (DR) is emerging as the leading cause of avoidable blindness worldwide. Methods : We reviewed previous and recent literature to provide an overview of emerging trends on the burden, epidemiology, risk factors, and prevention of DR. Results : First, there is clear evidence of a global increase in the prevalence of diabetes. Second, there is a decline in the incidence of blindness due to DR, particularly in developed countries. Third, diabetic macular edema (DME) rather than proliferative diabetic retinopathy (PDR) is the increasingly common cause of visual impairment. Fourth, DR awareness remains patchy and low in most populations. Fifth, hyperglycemia remains the most consistent risk factor for DR in type 1 diabetes across different studies and populations. Sixth, in contrast, blood pressure is an important risk factor for DR in type 2 diabetes. Seventh, the relationship between dyslipidemia and DR remains unclear, with inconsistent results from different studies and trials. Eighth, the utility of predictive models incorporating multiple risk factors for assessing DR risk requires evaluation. Ninth, photographic screening of DR using tele-ophthalmology platforms is increasingly recognized as being feasible and cost-effective. Finally, DR prevention in low-resource settings cannot follow models developed in high-resource countries and requires different strategies. Conclusions : The ten trends we observed in the current review may guide planning of public healthcare strategies for the management of DR and prevention of blindness.